2020
DOI: 10.1038/s41419-020-2277-7
|View full text |Cite
|
Sign up to set email alerts
|

α-Linolenic acid but not linolenic acid protects against hypertension: critical role of SIRT3 and autophagic flux

Abstract: Although dietary α-linolenic acid (ALA) or linolenic acid (LA) intake was reported to be epidemiologically associated with a lower prevalence of hypertension, recent clinical trials have yielded conflicting results. Comparable experimental evidence for the roles of these two different fatty acids is still lacking and the underlying mechanisms need to be further elucidated. Our data showed that ALA but not LA supplementation alleviated systolic blood pressure elevation and improved ACh-induced, endothelium-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…There are numerous studies which reported persistently increased ROS levels in HT, along with vast improvement upon antioxidative treatment [121][122][123][124][125][126][127]. HT is connected with vascular remodeling, increased vasoconstriction and arterial stiffness, activation of immune cells, renal dysfunction, and excitation of sympathetic nervous system.…”
Section: Hypertension and Oxidative Stressmentioning
confidence: 99%
“…There are numerous studies which reported persistently increased ROS levels in HT, along with vast improvement upon antioxidative treatment [121][122][123][124][125][126][127]. HT is connected with vascular remodeling, increased vasoconstriction and arterial stiffness, activation of immune cells, renal dysfunction, and excitation of sympathetic nervous system.…”
Section: Hypertension and Oxidative Stressmentioning
confidence: 99%
“…Effects of seminal ROS may be neutralized by the homeostatic antioxidant systems, to which belong manganese superoxide dismutase (SOD2), catalase (CAT), glutathione peroxidase 1 (GXP1), and glutathione S transferase (GST) [ 135 ]. This complex enzymatic kit was found also in endothelial cells [ 136 ]. In particular, SOD2 catalyzes the detoxification of superoxide radicals in H2O and O2 in mitochondria [ 136 , 137 ].…”
Section: Endothelial Function and Male Fertility: Endothelial Genementioning
confidence: 99%
“…This complex enzymatic kit was found also in endothelial cells [ 136 ]. In particular, SOD2 catalyzes the detoxification of superoxide radicals in H2O and O2 in mitochondria [ 136 , 137 ]. Although the gene sequences encoding these enzymes are phylogenetically conserved, SNPs could modulate their expression levels [ 136 ] and, consequently, interfere with the ROS/antioxidants balance, influencing male fertility [ 136 , 137 ].…”
Section: Endothelial Function and Male Fertility: Endothelial Genementioning
confidence: 99%
“…ALA administration to primary cultured endothelial cells induced inhibitions of NAD-dependent deacetylase sirtuin-3 (SIRT3) reduction, superoxide dismutase 2 (SOD2) hyperacetylation, and mitochondrial reactive oxygen species (ROS) overproduction, alongside restoration of autophagic flux under damage induced by treatment with angiotensin II plus TNFα [ 42 , 43 ]. Such effects, apparently attributed to ALA, are in line with mitigation of endothelial dysfunction and experimental hypertension [ 42 ].…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…Moreover, substrates for TG synthesis are also decreased by reduced transport of non-esterified fatty acids to hepatocytes, consequently reducing VLDL-C synthesis [ 44 , 48 ]. Nonetheless, as the majority of the cardiometabolic pathways so far elucidated are based on experimental data [ 40 , 41 , 42 , 43 ], a more thorough, critical and applied appraisal of the effects of ALA is needed before any general conclusions can be made.…”
Section: Metabolic Pathwaysmentioning
confidence: 99%